Evaluation of ubiquitin C-terminal hydrolase-L1 enzyme levels in patients with epilepsy - Ibrahim Halil YASAK; Mustafa YILMAZ; Murat GÖNEN; Metin ATESCELIK; Mehtap GURGER; Nevin ILHAN; Mehmet Cagri GOKTEKIN (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: Ubiquitin C-terminal Hydrolase-L1 (UCH-L1) enzyme levels were investigated in patients with epilepsy, epileptic seizure, remission period, and healthy individuals. Methods: Three main groups were evaluated, including epileptic seizure, patients with epilepsy in the non-seizure period, and healthy volunteers. The patients having a seizure in the Emergency department or brought by a postictal confusion were included in the epileptic attack group. The patients having a seizure attack or presenting to the Neurology outpatient department for follow up were included in the non-seizure (remission period) group. Results: The UCH-L1 enzyme levels of 160 patients with epilepsy (80 patients with epileptic attack and 80 patients with epilepsy in the non-seizure period) and 100 healthy volunteers were compared. Whereas the UCH-L1 enzyme levels were 8.30 (IQR=6.57‒11.40) ng/mL in all patients with epilepsy, they were detected as 3.90 (IQR=3.31‒7.22) ng/mL in healthy volunteers, and significantly increased in numbers for those with epilepsy (p<0.001). However, whereas the UCH-L1 levels were 8.50 (IQR=6.93‒11.16) ng/mL in the patients with epileptic seizures, they were 8.10 (IQR=6.22‒11.93) ng/mL in the non-seizure period, and no significant difference was detected (p=0.6123). When the UCH-L1 cut-off value was taken as 4.34 mg/mL in Receiver Operating Characteristic (ROC) Curve analysis, the sensitivity and specificity detected were 93.75 and 66.00%, respectively (AUG=0.801; p<0.0001; 95%CI 0.747‒0.848) for patients with epilepsy. Conclusion: Even though UCH-L1 levels significantly increased more in patients with epilepsy than in healthy individuals, there was no difference between epileptic seizure and non-seizure periods.